2021
DOI: 10.2459/jcm.0000000000001229
|View full text |Cite
|
Sign up to set email alerts
|

Long-term consequences of previous preeclampsia and complicated pregnancy: analysis of echocardiographic aspects

Abstract: Aim To evaluated echocardiographic aspects in women with history of preeclampsia or preeclampsia-related complications in their previous pregnancies. Materials and methods Consecutive women receiving echocardiography during daily clinical echolab activity were studied using complete echocardiographic examination data and anamnestic data collection of hypertension, diabetes, dyslipidemia, and rheumatic diseases. Studied women should have at least one pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Supplementary Figures S1, S2, and Supplementary Table S1 describe the demographics of the pregnant women, the distribution of BMI, and GA at delivery. Figure 2 represents the interconnectedness of APOs and RFs in our dataset based on Spearman correlation, confirming known relationships between APORFs established in prior studies ( 26 , 34 37 ). There are biological underpinnings to these correlations; for instance, prior studies found that TGF-β is a common biological factor between preeclampsia and diabetes ( 38 , 39 ).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Supplementary Figures S1, S2, and Supplementary Table S1 describe the demographics of the pregnant women, the distribution of BMI, and GA at delivery. Figure 2 represents the interconnectedness of APOs and RFs in our dataset based on Spearman correlation, confirming known relationships between APORFs established in prior studies ( 26 , 34 37 ). There are biological underpinnings to these correlations; for instance, prior studies found that TGF-β is a common biological factor between preeclampsia and diabetes ( 38 , 39 ).…”
Section: Resultssupporting
confidence: 83%
“…Although APOs are comparably rare, and thus challenging to model, their biological relationship and frequent presence as comorbidities provide an avenue for joint modeling approaches like MML to increase predictive power. As mentioned in the introduction, hypertension during pregnancy is correlated with diabetes and BMI; gestational diabetes is connected to hypertensive disorders, preeclampsia, and PTB; and prior preeclampsia is tied to an increased risk of hypertension and diabetes ( 26 , 27 , 34 ). As shown by our results, MML successfully models APOs simultaneously, outperforming single task approaches.…”
Section: Discussionmentioning
confidence: 99%
“…46 The exact mechanisms linking preeclampsia to heart failure risk are still being studied, but it is believed that the cardiovascular changes during pregnancy may have long-term effects on heart health. 47,48 A common pathophysiological pathway has been identified linking preeclampsia and fetal growth retardation (FGR) to the development of heart failure with preserved ejection fraction (HFpEF) later in life. This pathway involves several interconnected mechanisms, including chronic inflammation, oxidative stress, vascular biological aging, and myocardial subclinical involvement.…”
Section: Before Pregnancymentioning
confidence: 99%
“…These changes are accentuated in women with concurrent gestational hypertensive disorders. Among asymptomatic women delivered for preterm preeclampsia, over half have echocardiographic evidence of moderate to severe left ventricular dysfunction or hypertrophy and one year after delivery 99,100 . These cardiac changes are likely precipitated by increased arterial stiffness, increased peripheral resistance, and resultant increased cardiac output that are both characteristic of preeclampsia and…”
Section: The Impact Of Placenta-related Disorders On Maternal Cardiov...mentioning
confidence: 99%
“…Among asymptomatic women delivered for preterm preeclampsia, over half have echocardiographic evidence of moderate to severe left ventricular dysfunction or hypertrophy 1 year after delivery. 103,104 These cardiac changes are likely precipitated by increased arterial stiffness, increased peripheral resistance, and resultant increased cardiac output that are both characteristic of preeclampsia and proportional to the duration and severity of the condition. 103,[105][106][107][108] One year after delivery, women with history of preeclampsia have higher SBP and DBP, higher insulin levels, higher elevated total and low-density lipoprotein cholesterol levels and detectable microalbuminuria.…”
Section: Maternal Blood Pressure Is a Central Factor For Pregnancy Ou...mentioning
confidence: 99%